The Importance of Suicide Risk Formulation in Schizophrenia - Berardelli, Isabella; Rogante, Elena; Sarubbi, Salvatore; Erbuto, Denise; Lester, David; Pompili, Maurizio (Frontiers in Psychiatry, 2021)
Suicide is a cause of early mortality in nearly 5% of patients with schizophrenia, and 25–50% of patients with schizophrenia attempt suicide in their lifetime. Evidence points numerous individual, clinical, social, and psychological risk factors for suicide in patients with schizophrenia. Although recognizing suicidal risk factors in schizophrenia is extremely important in suicidal risk assessment, we have recently witnessed a change in suicide risk management that shifts the focus from suicide risk assessment to suicide risk formulation. Suicide risk formulation is dependent on the data gathered in the suicide risk assessment and assigns a level of suicide risk that is indispensable for the choice of treatment and the management of patients with a high suicidal risk. In this article, we extend the suicide risk formulation model to patients with schizophrenia. Suicide risk formulation results from four different areas that help clinicians collect as much information as possible for the management of suicidal risk. The four distinct judgments comprise risk status (the risk relating to the specific group to which the patient belongs), risk state (the risk for the person compared with his baseline or another reference point in the course of his life), available resource (on whom the person can count during a crisis) and foreseeable events (which can exacerbate the crisis). In schizophrenia, the suicide risk formulation model allows the clinician to evaluate in depth the clinical context of the patient, the patient’s own history and patient-specific opportunities for better choosing and applying suicide prevention strategies.